Camassa-Holm equation: transformation to deformed sinh-Gordon equations, cuspon and soliton solutions - Kraenkel, Roberto André [UNESP]; Zenchuk, A. (Iop Publishing Ltd, 1999)
In this paper a relation between the Camassa-Holm equation and the non-local deformations of the sinh-Gordon equation is used to study some properties of the former equation. We will show that cuspon and soliton solutions can be obtained from soliton solutions of the deformed sinh-Gordon equation.